Divergências morfométricas e comportamentais em Apis mellifera L. (Hymenoptera:apidae) - Sousa, Arlik Rafael Santiago de (2014)
Bees of the genus Apis are widely distributed throughout the tropical regions of the planet, playing fundamental role as pollinators. In Brazil they are a polihibrid formed by the crossbreed of African subspecies Apis mellifera scutellata and European subspecies, where due generalist habits the introgression of alleles of the African subspecies has led to a predominance of the your characteristics in relation to European subspecies. The scope of this work was to characterize the divergence among 71 colonies of Africanized honey bees located in three distinct ecoregions (Forest zone, Ecotone and Semiarid) of the State of Sergipe Brazilian northeast, through morphological and behavioral analyses, in order to assess the relationship between the effects of seasonality and the different patterns morphoclimatic ecoregions in morphology, behavior and distribution of these groups of bees. In this work we used geometric morphometric techniques observing the anatomical landmarks of the wing venation with the aid of software Tps / DIG and evaluation of hygienic behavior by pin-killing method in two distinct seasonal periods, the dry and rainy. The correlation between the hygienic behavior indexes and environmental variables was obtained by Spearman correlation and the causal relations by path analysis, with the aid of software R. The morphometric analyzes were performed by means of multivariate analysis with the aid of software MORPHOJ and PAST. Thus, the results of this study demonstrated that the high gene flow evidenced between studied colonies and pronounced differences in apiaries and ecoregions with influence of altitude on shape (r=0,06239; p= 0.05) and size (0.001) contributed therefore for the separation of these groups as result of phenotypic plasticity rather than genetic divergence among populations of Africanized honey bees. Furthermore, the results also demonstrated significant difference in hygienic behavior of these populations between the dry and rainy season (p= 0,022; α=0,05) and between ecoregions (p=0,001; α=0,05) with the influence of temperature (ρ=0,065; p=0,471; α=0,05) and altitude (ρ=-0,294; p=0,001 α=0,05) upon pluviosity (ρ=0,274; p=0,002; α=0,05) that demonstrated be the main modulator of hygienic behavior, thus reinforcing the influence of environmental factors on the expression of this trait. Therefore, it is concluded by the influence of stochastic factors in the morphology, behavior and distribution of Africanized honey bees, where polyphenisms found denote the high genetic variability of these populations, a fact that can be exploited in future conservation, handling and breeding programs.